Capturing a Pentacyclic Fragment‐Based Library Derived from Perophoramidine: Their Design, Synthesis and Evaluation as Anticancer Compounds by DNA Double‐Strand Breaks (DSB) and PARP‐1 Inhibition. Issue 63 (7th September 2022) - Guha, Souvik; Yussif El‐Deeb, Ibrahim; Yadav, Shalini; Das, Ranajit; Dutta Dubey, Kshatresh; Baruah, Mousumi; Gremaud, Ludovic; Sen, Subhabrata
Abstract: Herein we have reported the discovery of a pentacyclic building block comprised of fused indole‐quinoline and piperidinone from the natural product perophoramidine as a formidable anticancer agent. The compounds were synthesized in six steps where the key steps involved a blue LED mediated intramolecular cyclopropanation of the indole intermediates and concomitant reduction of the associated aryl nitro moiety to nitroso in the molecule. Cytotoxicity screening of the compounds against an array of cancer cells that is, MCF7, HCT116 and A549 demonstrated 0.6 to 9 μM IC50 s by few of the compounds. γH2AX immunofluorescence assay of the two most potent molecules from the phenotypic screening with anti‐γ‐H2AX Alexa Fluor 488 antibody revealed extensive DNA damage of the A549 cells which indicated probable PARP inhibition (similar to Perophoramidine). Through molecular docking and molecular dynamic (MD) simulation studies the binding efficiency of our compounds with poly(ADP‐ribose)polymerase 1 (PARP 1) enzyme was determined. Chemiluminescent PARP Assay with Histone‐coated strips indicated that the most active compounds from the phenotypic screening induced PARP‐1 inhibition with IC50 s of 1.3→1.5 μM. Abstract : A Pentacyclic fragment inspired from Perophoramidine. Natural product inspired PARP inhibitor.